ECONOMIC ADVANTAGES OF INTEGRATING CULTURAL HERITAGE INTO EARLY LANGUAGE EDUCATION - Sultanova Shohistaxon Shavkatovna (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Annotation: This article explores the economic benefits of incorporating cultural heritage into early language education programs. It argues that integrating local traditions, history, and cultural expressions within language instruction not only enriches students’ learning experiences but also strengthens community identity and social cohesion. By fostering a deeper connection to cultural roots, such education enhances motivation and academic success, which in turn contribute to improved human capital development. The paper also highlights how culturally informed language education supports sustainable economic development by promoting cultural tourism, creative industries, and the preservation of intangible cultural assets. Policy implications for education systems aiming to balance cultural preservation with economic growth are discussed.